The Problem of the Sustainability Communication: Media Factor - Savickas, Mindaugas (Žurnalistikos tyrimai, 2017)
In this article sustainable development concept is viewed as a Dialogue of values – alternative for sustainable development as Ethical Consensus and Technical Consensus approaches, as proposed by sociologist Blake D. Ratner. This alternative of sustainable development interfere with fundamental values of media system – freedom, equal rights, and diversity. Assessing perspectives of sustainable development, as a dialogue of values realization in broad social – cultural, politic – economic, environmental fields, it is important to understand impact of media factor, which is critically important in modern word. The quality of the whole media system and the quality of media content affects understanding and implementation of sustainability ideas in politics of the state and wide society. Responsible, complex and creative representation of sustainability and its issues in the media would increase knowledge in broad societies, and would affect both public and political agenda in sustainable way. Alternatively, media work without deep understanding and rich representation of sustainability puts in doubt perspectives of sustainability. It is argued, that news culture, driven by drama, conflict, personalities and some other “news values” is a major barrier for sustainability communication in media field and puts in doubt perspective of sustainable development as a Dialogue of values.